Formative research in the development of communicative and investigative skills - García Bedoya, García Bedoya (2018)
The research sought to apply formative research, using strategies such as information gathering, research seminar and monograph to improve communication and research skills in university students. These strategies were linked to a profile of a promoter teacher that manages research methodology and incorporates it into their pedagogical practice. The research corresponds to the quantitative approach and the experimental level, with a quasi-experimental design with pre- and post-test. The sample consisted of 77 students (experimental group) and 63 (control group), who were applied pre and post test to measure their communication skills (listening, speaking, reading and writing) and investigative (observe, describe, analyze, synthesize and interpret). The instruments used to collect data were the written test and the rubric. The statistical analysis was based on the difference of means with Z distribution, with a confidence level of 95.0%. The results reflect that formative research has positive effects in the development of communicative and investigative skills; having passed, after the experiment, the qualifications obtained in the pre-test at 4.12 points, going from a poor level to a good level. In terms of communication skills, knowing how to speak and know how to write were the ones that developed the most. In relation to investigative skills, the ones that developed the most were analysis, synthesis and interpretation. These results show that, due to its effectiveness, formative research must become a permanent and gradual activity in university education.